QUALITY OF LIFE INDICATORS FOR CHILDREN WITH HIGH THROMBOGENIC RISK FACTORS - Лилия Александровна Елизарьева (Мать и дитя в Кузбассе, 2020)
The study of quality of life (QOL) in medicine is a unique approach that allows you to fundamentally change the traditional view of the problem of health status and comprehensively study the indicators of human quality of life, evaluating all components of health – physical, psychological and social functioning. The study was conducted on the basis of the «Health Center for Children» (CH) of Barnaul, it includes 396 children. Of these, there were 169 (42.9 %) boys and 226 (57.1 %) girls. The average age of the examined children was 15.2 ± 2.3 years. Assessment of the quality of life of children with high thrombogenic risk factors and the comparison group showed that in the comparison group there were no statistically significant differences in the quality of life before the examination in the CH and 6 months after. And in the group of children with high thrombogenic risk factors, there was a significant improvement in the EF (emotional functioning ) (from 62 to 75 points) and LS (life at school) (from 61 to 74 points) (p < 0.05), while the PF (physical functioning) and SF (social functioning ) indicators did not statistically significantly change The most pronounced symptoms in all the children examined according to the MDASI questionnaire are pain, a feeling of sadness and weakness. These symptoms affected the mood of the children and their ability to enjoy life, as well as their general activity and attitude with other children.